Direct polymerization of aromatic diacid dimethyl esters with aromatic diamines .1. Analysis of reaction mechanism - Park, SK; Ha, WS; Lee, CJ (ELSEVIER SCI LTD, 1997)
The direct polymerization of aromatic diacid dimethyl esters with aromatic diamines using phosphorus activating agents and tertiary amines was conducted at room temperature. The reaction mechanism was investigated with model compounds. The diacid dimethyl ester of pyromellitic dianhydride was reacted with the activating agent, along with pyridine as a catalyst, or reacted with an N-methylpyrrolidone (NMP)-activating agent complex to form the activated anhydride intermediate. It was characterized with P-31 and H nuclear magnetic resonance, and ultra-violet-visible spectroscopy. The polymerization proceeded via the nucleophilic substitution reaction between aromatic acid and amine. The amidation reaction proceeded further to afford N-phenylphthalmide with phosphorus oxychloride and phenyl phosphonyl dichloride in the model reactions, but not in the polymerization reaction. As for the degree of polymerization, phenyl phosphonic dichloride and pyridine were superior to any other pairs of activating agent and tertiary amine. The direct polymerization of various diacid dimethyl esters of aromatic dianhydrides with aromatic diamines was successfully performed. (C) 1997 Elsevier Science Ltd.
Keywords: DIRECT POLYCONDENSATION; POLYAMIC ACID; POLYIMIDE